2010
DOI: 10.2146/ajhp090303
|View full text |Cite
|
Sign up to set email alerts
|

Periorbital edema associated with separate courses of ibuprofen and naproxen

Abstract: An elderly woman developed periorbital edema after taking ibuprofen on one occasion and naproxen on another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
1
Order By: Relevance
“…Hence, the effect of indomethacin on sodium excretion was explained by inhibition of PGs. Similarly, Balas et al reported a case of periorbital edema induced by both ibuprofen and naproxen used on separate occasions (105).…”
Section: Electrolyte and Fluid Retentionmentioning
confidence: 89%
“…Hence, the effect of indomethacin on sodium excretion was explained by inhibition of PGs. Similarly, Balas et al reported a case of periorbital edema induced by both ibuprofen and naproxen used on separate occasions (105).…”
Section: Electrolyte and Fluid Retentionmentioning
confidence: 89%
“…In this view, all etiological factors should be under account to solve this disturbing symptom by the physicians [7,8]. The some medications associated with periorbital edema such as aspirin, naproxen, ibuprofen, nifedipine, diltiazem, midazolam, topiramate, irbesartan, lamotrigine, niacin, omeprazole, pantoprazole, diltiazem, nifedipine, phenytoin, phenobarbital, hydrochlorothiazide, imanitib and risperidone previously had been reported [10][11][12][13]. In some previous case report, peripheral edema associated with mirtazapine was declared [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Several older drugs, such as ibuprofen, naproxen [98], and aspirin [99], have also been implicated in isolated edema of the eyelids. Some antipsychotics such as risperidone [100] and clozapine [101] can also cause eyelid edema, although these reactions are considered rare.…”
Section: Medicationmentioning
confidence: 99%
“…One patient had dependent edema after a craniotomy for a brain tumor. Medications associated with periorbital edema Clozapine [101] Hyaluronidase [97,108] Sulfite [105] Pemetrexed [109] Zoledronic acid [95] Diltiazem [110] Risperidone [100,111] Aspirin [99,112,113] Doxorubicin [107] Imatinib [93,94,[114][115][116] Irbesartan [103] Atracurium [117] Ibuprofen [98,118,119] Epoxy resin [120] Nifedipine [102] Naproxen [98] Lamotrigine [104] Cisplatin [106] Ethosuximide [106] Fluorouracil [106] Hydralazine [106] Metformin [106] Methotrexate [106] Methsuximide [106] Oprelvekin [106] Pioglitazone [106] Rifampicin [106] Rosiglitazone [106] Smallpox vaccine [106] Sulfacetamide [106] Sulfafurazole [106] Sulfamethizole [106] Sulfanilamide [106] Sulfasalazine [106] Sulfathiazole [106] Topiram...…”
Section: Retrospective Case Reviewmentioning
confidence: 99%